1990 Atlantic Universities Geological Conference: Abstracts November 1-4, 1990

(untitled) (Atlantic Geoscience Society, 1990)
Again this year, abstracts from the annual Atlantic Universities Geological Conference are published in "Atlantic Geology." This provides a permanent record of the abstracts, and also focuses attention on the excellent quality of and interesting and varied science in these presentations.